Effect of Key Audit Matters Disclosure on the Financial Reporting Quality of Deposit Money Banks in Nigeria. - Alaji John; Joshua Okpanachi; Idachaba, Armstrong Aduku; Musa, Success Jibrin (Educational Administration: Theory and Practice, 2025)
Financial reporting is the cornerstone of transparency and accountability in corporate governance. For Deposit Money Banks (DMBs), financial statements are particularly important because they provide critical information about liquidity, solvency, risk exposures, and overall financial health. In Nigeria, where banks play a pivotal role in financial intermediation and economic development, the credibility of financial reporting is central to sustaining confidence among depositors, investors, regulators, and the general public (Central Bank of Nigeria, 2022). High-quality financial reporting is characterized by relevance, reliability, comparability, and faithful representation. However, in practice, concerns about earnings management, delayed loss recognition, and poor disclosure practices have cast doubts on the reliability of financial reports issued by Nigerian banks (Okafor & Oghoghomeh, 2020). To strengthen stakeholders’ trust and improve transparency, external auditors play a critical role by independently verifying whether financial statements give a true and fair view. The International Auditing and Assurance Standards Board (IAASB), in response to global calls for more informative auditor reports, introduced International Standard on Auditing (ISA) 701: Communicating Key Audit Matters (KAMs). Effective from December 2016, ISA 701 requires auditors of listed entities to disclose in their audit reports the matters of most significance during the audit of the financial statements. These KAMs typically include complex accounting estimates, valuation judgments, and areas requiring significant auditor attention (IAASB, 2015). The expectation is that KAMs will enhance the communicative value of audit reports, reduce the information gap between auditors and users, and ultimately improve financial reporting quality. Empirical studies on the impact of KAMs have show mixed findings. While some evidence suggests that KAMs improve audit transparency and constrain opportunistic financial reporting (Gold, 2020), other studies argue that disclosures are often boilerplate, generic, and of limited informational value (Sirois, Bédard & Bera, 2018). In Nigeria, preliminary findings show that although auditors comply with ISA 701, many KAM disclosures are repetitive and lack entity-specific insights, raising concerns about their effectiveness in improving reporting quality (Emeh & Appah, 2021). The Nigerian banking sector provides an important context for examining this issue. Banks’ financial reports are complex, involving significant judgment in areas such as loan-loss provisioning, fair value measurement, and impairment assessments. These areas are also among the most frequently reported KAMs, making banks an ideal sector for evaluating the usefulness of KAM disclosures. Moreover, given Nigeria’s history of banking crises, corporate failures, and weak governance, it is crucial to determine whether KAM reporting has achieved its intended objective of enhancing the quality and credibility of financial reporting.